2023
DOI: 10.31643/2024/6445.23
|View full text |Cite
|
Sign up to set email alerts
|

Digitalization of the thermoplastic beryllium oxide slurry forming process using ultrasonic activation

U. Zhapbasbayev,
G. Ramazanova,
H. Retnawati
et al.

Abstract: This paper presents the results of the digitalization of the thermoplastic beryllium oxide slurry forming process using ultrasonic activation. Ceramics made from beryllium oxide (BeO) using ultrasound-assisted forming exhibit more intense sintering and, in comparison to ceramics formed without ultrasound, have reduced shrinkage (by 2.4-4.3%) and sintering temperature (by 50-180°C). The forming processes occurring during ultrasonic treatment resulted in the homogenization of the thermoplastic suspension and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…New alloys have increased strength, ductility, heat resistance, corrosion resistance, variable crystal size in the matrix, and other properties. These magnesium materials include additives of manganese [ [4], [5], [6], [7], [8], and [9]], zirconium [ [10], [11], [12], [13], [14], [15], [16], [17], and [18]] and beryllium [ [19], [20], [21], [22], [23], [24], and [25]].…”
Section: Introductionmentioning
confidence: 99%
“…New alloys have increased strength, ductility, heat resistance, corrosion resistance, variable crystal size in the matrix, and other properties. These magnesium materials include additives of manganese [ [4], [5], [6], [7], [8], and [9]], zirconium [ [10], [11], [12], [13], [14], [15], [16], [17], and [18]] and beryllium [ [19], [20], [21], [22], [23], [24], and [25]].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research endeavors have aimed to address these challenges (Sheriyev et al, 2016;Retnawati, 2017;Zhapbasbayev et al, 2021;Rohde et al, 2023;Zhapbasbayev et al, 2024). The utilization of human-machine interfaces (HMIs) , mobile applications (Santosh et al, 2016), and online feedback tools on computers (Samuel et al, 2014) has shown promise in improving thermal comfort, energy efficiency, and environmental well-being by gathering user thermal comfort data.…”
Section: Introductionmentioning
confidence: 99%